Young homeless people and urban space: fixed in mobility - Jackson, Emma (Routledge advances in ethnography, 2015)
Introduction: "London is THE city" -- Almost home?: the production of the day centre -- In the same boat?: the production and negotiation of super-diverse homeless space -- Demanding accounts? -- Making tracks, mobile lives -- Surveillance and the limits of reorientation -- The hostel: mooring and meshing -- Imagined futures, precarious presents and persistent pasts -- Conclusions